A Principal-Agent Theory Approach to Public Expenditure Management Systems in Developing Countries - Leruth, Luc (IMF Working Papers; Working Paper ;, 2006)
A well-functioning public expenditure management (PEM) system is considered a critical pillar of government efficiency, on par with a low-distortion tax system and efficient tax administration. The paper discusses PEM systems in developing countries using an analytical framework based on principal-agent theory. This simple model can be applied to various PEM systems, and allows for comparisons between institutional settings. To illustrate this, we analyze the benefits derived from the use by the Ministry of Finance (MoF) of two control instruments; ex post audits and ex ante controls, and assess their value in terms of their ability to deter cheating. We derive a set of possible "control regimes" which can be used by the MoF. Although we illustrate the use of the model using developing countries, it is also relevant to developed economies.